Inhibition of Pseudomonas aeruginosa Biofilm Formation and Quorum Sensing System by Extracts of Prunus avium Stalk - (:unkn) unknown (My University, 2021)
Recently, misuse or overuse of antibiotics has led to antibiotic resistance problem, a global healthcare problem. Most virulencefactors and biofilm formation in Pseudomonas aeruginosa are controlled by quorum sensing (QS). The inhibition of QS systemby inhibitor molecules has been suggested as a novel alternative antivirulence approach in which no need to kill the bacteria.In the present study, QS and biofilm inhibitory potentials of the methanol and acetone extracts of Prunus avium stalk againstP. aeruginosa were evaluated. The extracts were tested at the concentrations of 240, 120, and 60 μg/ml. lasB-gfp, rhlA-gfp,pqsA-gfp biosensor strains and P. aeruginosa PAO1 were used to monitor QS and biofilm inhibition, respectively. Fluorescenceand absorbance measurements were performed on Cytation 3 multimode microplate reader. QS inhibition ratios for las, rhl,and pqs systems and biofilm inhibition ratios of the acetone extracts were recorded as 70.43%, 47.25%, 76.31%, and 47.76%(±6,60) and of the methanol extracts as 74.96%, 40.10%, 71.89%, and 38.54% (±3,56) at a certain concentration of 240 μg/ml,respectively. As a result, anti-QS and anti-biofilm properties of acetone extracts were better than that of methanol extracts.Further investigations are needed to discover inhibitor compounds of P. avium and also their effects on human cells and thenthese compounds may be used in new drug discoveries.

Son zamanlarda, antibiyotiklerin yanlış veya aşırı kullanımı, küresel bir sağlık sorunu olan antibiyotik direnci sorununa yol_x000D_ açmıştır. Pseudomonas aeruginosa'da çoğu virülans faktörü ve biyofilm oluşumu, quorum sensing (QS) ile kontrol edilir. QS_x000D_ sisteminin inhibitör moleküller tarafından inhibisyonu, bakterileri öldürmeye gerek olmayan yeni bir alternatif antivirulens_x000D_ yaklaşımı olarak önerilmiştir. Bu çalışmada, Prunus avium sapından elde edilen metanol ve aseton özütlerinin P. aeruginosa'ya_x000D_ karşı QSI (QS inhibitörleri) ve anti-biyofilm potansiyellerini değerlendirdik. Ekstraktlar 240, 120 ve 60 μg/ml'lik_x000D_ konsantrasyonlarda test edilmiştir. QS ve biyofilm inhibisyonunu izlemek için lasB-gfp, rhlA-gfp, ve pqsA biyosensör suşları_x000D_ ve P. aeruginosa PAO1 kullanıldı. Floresans ve absorbans ölçümleri Cytation 3 çok modlu mikroplaka okuyucu üzerinde_x000D_ gerçekleştirildi. 240 μg/ml konsantrasyonunda aseton özütlerinin las, rhl ve pqs sistemleri üzerine QS ve biyofilm inhibisyon_x000D_ oranları sırasıyla % 70.43, % 47.25, % 76.31 ve % 47.76 (± 6,60) ve metanol özütlerinin sırasıyla % 74.96, % 40.10, % 71.89_x000D_ ve % 38.54 (± 3,56) olarak kaydedilmiştir. Sonuç olarak, aseton özütlerinin anti-QS ve anti-biyofilm özellikleri metanol_x000D_ özütlerinden daha başarılı olmuştur. P. avium’un inhibitör bileşikleri ve bu bileşiklerin insan hücreleri üzerindeki etkilerini_x000D_ keşfetmek için daha fazla araştırmaya ihtiyaç vardır ve daha sonra bu bileşikler yeni ilaç keşiflerinde kullanılabilir.
Prunus avium Sapından Elde Edilen Özütlerle Pseudomonas aeruginosa’ya ait Quorum Sensing Sisteminin ve Biyofilm Oluşumunun İnhibisyonu